2016
DOI: 10.1007/s00256-016-2475-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 3-T magnetic resonance imaging with 3D T1 VIBE versus computer tomography in pars stress fracture of the lumbar spine

Abstract: 3-T MRI with thin-slice 3D T1 VIBE is 100 % accurate in diagnosing complete pars fractures and has excellent diagnostic ability in the detection and characterization of incomplete pars stress fractures compared to CT. MRI has the added advantages of detecting bone marrow edema and does not employ ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…Furthermore, specific MRI sequences, such as the volumetric interpolated breath-hold examination (VIBE) have proven to be particularly sensitive in the detection of bone marrow oedema, stress fractures and other sports-related osseous pathology. VIBE images permit high-quality imaging of bone tissue with superior spatial resolution 23 24. In our case, the use of MRI facilitated prompt diagnosis and enabled appropriate intervention, without which it is plausible that she would have progressed to develop a stress fracture.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, specific MRI sequences, such as the volumetric interpolated breath-hold examination (VIBE) have proven to be particularly sensitive in the detection of bone marrow oedema, stress fractures and other sports-related osseous pathology. VIBE images permit high-quality imaging of bone tissue with superior spatial resolution 23 24. In our case, the use of MRI facilitated prompt diagnosis and enabled appropriate intervention, without which it is plausible that she would have progressed to develop a stress fracture.…”
Section: Discussionmentioning
confidence: 70%
“…15 More recently, however, a study by Ang et al in 2016 utilizing 3D T1 volumetric interpolated breath-hold examination (VIBE) reported an excellent 100% accuracy in detecting complete pars fractures, with a very respectable 97.7% sensitivity and 92.3% specificity in detecting partial pars fractures. 31 The improved accuracy by Ang et al can be partly attributed to the higher strength 3-T MRI (versus 1-T MRI by Campbell et al). A VIBE sequence relies on marrow discontinuity and sclerosis as a sign of a pars defect.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 98%
“…Although CT is excellent for confirming the presence and determining the extent of a pars defect (after a positive bone scan or MRI for instance), as well as assessing bony healing, it is less useful than both bone scintigraphy and MRI for distinguishing early stress reaction, as well as active healing fractures from inactive chronic nonunion. Furthermore, even when optimized to image only the level of interest, CT exposes the patient to ionizing radiation, which is of particular concern in this young patient population [3].…”
Section: Imagingmentioning
confidence: 99%
“…Ang et al [3] recently compared 3T MRI using a thin‐slice 3D T1 VIBE sequence versus CT in the detection and grading of pars injuries. The authors found that with use of a 3T magnet and a 3D T1 VIBE sequence, MRI can provide accurate assessment of pars bone morphology and pathology with findings comparable to CT.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation